(untitled) (International Journal of Food and Nutritional Sciences, 2025)
This paper will discuss how employee retention policies and managerial competence correlate in e-business firms working in rural Raipur, Chhattisgarh, India and fill a gap in the literature of human capital development in emerging digital economies. The mixed-methods research design was employed to gather data on 267 respondents in 58 e-business firms by use of structured questionnaires and 30 in-depth interviews and analyzed using descriptive statistics, correlation analysis, multiple regression, and structural equation modeling. The results demonstrate that the policies of workforce retention jointly predict 58.7% of the variance in managerial competence (R 2 = 0.587, p < 0.001), and career development opportunities appeared to be the best predictor ( 0.286, p = 0.001), then organizational culture ( 0.241, p = 0.001), and work environment ( 0.198, p = 0.001). The paper shows that rural e-business companies have a strategic focus on developmental and cultural retention systems, rather than financial rewards, as a response to scarcity of resources, and as a way of achieving a desired impact on resource utilization, by enabling managerial competencies, through employee stability and ensuring knowledge acquisition. Analysis of mediation dictates that retention policies result in employee competence through the mediating variable that is employee satisfaction ( 0.432, p < 0.001) and organizational commitment ( 0.389, p < 0.001). There is a notable difference between firm sizes suggesting that medium enterprises share a significantly outstanding level of retention policy implementation and managerial competence than micro and small ones, which reflects capacity-related issues in smaller organizations. The study determines competence mediums in strategic orientation and innovation capability and higher score in operational management with recommended areas that can be specifically developed. These results can help rural e-business professionals to develop retention strategies that involve career development and organizational culture, and explain to policymakers that sustainable development of managerial competence requires supportive interventions in the retention capacity of the smaller businesses to promote sustainable development of managerial competence in rural digital entrepreneurship environments.